2011
DOI: 10.1103/physrevb.84.085209
|View full text |Cite
|
Sign up to set email alerts
|

Importance of intramolecular electron spin relaxation in small molecule semiconductors

Abstract: Electron spin relaxation rate (eSR) is investigated on several organic semiconductors of different morphologies and molecular structures, using avoided level crossing muon spectroscopy as a local spin probe. We find that two functionalized acenes (polycrystalline tri(isopropyl)silyl-pentacene and amorphous 5,6,11,12-tetraphenyltetracene) exhibit eSRs with an Arrhenius-like temperature dependence, each with two characteristic energy scales similar to those expected from vibrations. Polycrystalline tris(8-hydrox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…The intermolecular distance and interactions may affect the orbital overlap of the p electrons in OSs 40 , which determine the transport efficiency of the charge carriers. Previous studies have also reported that temperature affects the lattice fluctuations 41,42 and intramolecular interactions 30,43 of C 60 , which may cause variations in the s-orbital. The s-orbital affects the SDT length in organic OSs 38 .…”
Section: Resultsmentioning
confidence: 99%
“…The intermolecular distance and interactions may affect the orbital overlap of the p electrons in OSs 40 , which determine the transport efficiency of the charge carriers. Previous studies have also reported that temperature affects the lattice fluctuations 41,42 and intramolecular interactions 30,43 of C 60 , which may cause variations in the s-orbital. The s-orbital affects the SDT length in organic OSs 38 .…”
Section: Resultsmentioning
confidence: 99%
“…4). We also believe that electron spin relaxation and/or spin exchange cannot account for these changes-as it is known to affect all ALCs in a similar fashion in the solid state 32,33 , there is no associated increase in relaxation rate and it cannot account for all of the features in the time-dependent data (see the Supplementary Information). To explain our observations, one must invoke the mechanism of radical formation from the solvated muonium.…”
Section: Light-induced Effects On Alc Spectramentioning
confidence: 99%
“…There could be a change in hyperfine coupling constant due to a structural or conformational difference 31 , an increased electron spin relaxation or exchange [32][33][34] , or a modification of the muonium reaction rate for a given carbon 31 . It is extremely unlikely that a conformational change or unpaired spin can account for this data, as the ALC at around 300 mT for site 4 is identical for the light-on and light-off cases.…”
Section: Light-induced Effects On Alc Spectramentioning
confidence: 99%
“…This latter species can then chemically bind to an unsaturated organic molecule, in a similar way to hydrogenation, and is an extremely sensitive probe of spin dynamics intrinsic to the molecule [5][6][7][8][9][10]. If an external magnetic field is applied in the direction of the initial muon spin, as it is in so called longitudinal field experiments, the Hamiltonian for muonium can be written as…”
Section: Muon Spin Relaxation and Avoided Level Crossingmentioning
confidence: 99%
“…However, spin phenomena in these materials are not yet fully understood, partly due to the lack of suitable characterisation techniques, since those extensively used to characterise inorganic semiconductors are not always applicable to organic materials [1][2][3]. Muon spin relaxation (mSR) has been proven to be an applicable probe in this field, as it is sensitive to spin dynamics in organic semiconductors on a molecular length scale [4][5][6][7]. In organic semiconductors the implanted muons form a hydrogen-like system, called muonium, by capturing an electron.…”
Section: Introductionmentioning
confidence: 99%